Layanan Bimbingan Kelompok Teknik Sosiodrama untuk Meningkatkan Keterampilan Komunikasi Siswa - Maisunah, Maisunah (Universitas Islam Negeri Madura, 2021)
Banyak siswa yang memiliki masalah dengan ketermpilan komunikasi lisannya, hal ini dapat di temukan di lingkungan sekolah mereka pada siswa kelas VII di MTs. An-Najah I. Berdasarkan hal tersebut, penelitian ini ingin mengetahui: Pertama bagaimana penerapan layanan bimbingan kelompok dengan metode sosiodrama dalam meningkatkan komunikasi lisan pada siswa kelas VII MTs. An-najah I Karduluk, kedua apa saja faktor pendukung dan penghambat dalam pelaksanaan layanan bimbingan kelompok dengan metode sosiodrama dalam meningkatkan komunikasi siswa pada siswa kelas VII MTs. An-Najah I karduluk. Metode penelitian yang digunakan adalah PTBK. Penelitian ini dilaksanakan di MTs. An-Najah I karduluk dengan subyek penelitian seluruh siswa kelas VII sebanyak 20 siswa. Penelitian ini dilaksanakan dengan 2 siklus dan setiap siklus memiliki 3 kali pertemuan. Teknik pengumpulan data yang digunakan adalah observasi, wawancara dan dokumentasi. Teknik analisis data pada penelitian ini adalah statistik deskriptif. Hasil penelitian ini menunjukkan bahwa teknik sosiodrama dapat meningkatkan kemampuan komunikasi lisan siswa kelas VII MTs An-Najah I. Peningkatan kemampuan komunikasi lisan sebelum tindakan sebesar 46.6. Pada siklus I diperoleh skor rata-rata sebesar 76.09, terjadi peningkatan skor sebesar 29.49. Pada Siklus II diperoleh skor rata-rata 88.40, terjadi peningkatan skor sebesar 12.31 dari siklus I. Sehingga diperoleh peningkatan skor sebesar 41.8 dari pra tindakan hingga siklus II. Faktor pendukung adalah suasana kelas yang kondusif, sedangkan faktor penghambatnya yaitu kurangnya alat-alat pendukung dalam pelaksanaan sosio drama.[Many students experienced oral communication skill problem. One of them is class VII students at MTs. An-Najah I who had low communication skill. Therefore, guidance and counseling services are needed to deliver by the school counselor. Group guidance service with sociodarama tecnique was considered to help increasing students’ communication skill. Based on that, there are two research focuses: First, how is the implementation of group guidance services using the sociodrama technique to improve students’ oral communication skill; second, what are the supporting and inhibiting factors in the implementation of group guidance service using the sociodrama technique in improving students’ communication skill. This research was an Action Guidance and Counseling Research in which conducted at MTs. An-Najah I Karduluk Sumenep with 20 students of grade VII as as the subjects. This research was carried out in 2 cycles and each cycle consist of 3 meetings. The data collection techniques were observation, interview, and documentation. Anda descriptive statistics used as the data analysis technique to find the average and qualitative descriptive analysis. The results of this study indicate that sociodrama technique can improve the oral communication skill of grade VII students of MTs An-Najah I. Students’ oral communication skill score before treatment was 46.6. Then in the first cycle they obtained an average score of 76.09, an increase in the score of 29.49. In Cycle II, an average score of 88.40 was obtained, there was an increase in the score of 12.31 from cycle I. Hence, the total increase was 41.8 from pre-action to cycle II. Moreover, supporting factors of the implementation of group guidance services using the sociodrama technique in improving students’ oral communication skill were a conducive classroom atmospherethe enthusiastic and excitement of the students. While the inhibiting factors were the lack of supporting and the restricted space for playing the sociodarama].